1988
DOI: 10.1017/s0950268800065547
|View full text |Cite
|
Sign up to set email alerts
|

The vertical transmission of salmonellas and formic acid treatment of chicken feed: A possible strategy for control

Abstract: The treatment of feed given to laying hens with 0.5% formic acid reduced significantly the isolation rate of salmonellas and was associated with a reduction in the incidence of infection in newly hatched chicks. These improvements were not sustained until slaughter, however, as growing birds acquired salmonellas, probably from feed which was not acid treated. The data indicate that formic acid treatment of chicken food could have important benefits for the public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 7 publications
0
33
0
2
Order By: Relevance
“…In their experiments, these authors used desiccated coconut as a premix for the addition of Salmonella kedougou to feed and it may be that such relatively large particles harboured many more organisms than this giving a falsely low impression of the true viable number in the feed. It must be said that other authors have also found little effect on Salmonella viability in feed (Khan & Katamay, 1969;Duncan & Adams, 1972;Vanderwal, 1979;Humphrey & Lanning, 1988). Since these authors all used naturally, as opposed to experimentally contaminated feed, this difference may account for the discrepancy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In their experiments, these authors used desiccated coconut as a premix for the addition of Salmonella kedougou to feed and it may be that such relatively large particles harboured many more organisms than this giving a falsely low impression of the true viable number in the feed. It must be said that other authors have also found little effect on Salmonella viability in feed (Khan & Katamay, 1969;Duncan & Adams, 1972;Vanderwal, 1979;Humphrey & Lanning, 1988). Since these authors all used naturally, as opposed to experimentally contaminated feed, this difference may account for the discrepancy.…”
Section: Discussionmentioning
confidence: 92%
“…Use of 0.5% formic acid in feed in a breeder unit reduced contamination of progeny chick tray liners by 5. entérinais by 75% and hatchery waste by 94% (Humphrey & Lanning, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…in poultry are described but most require more large scale field evaluations (Van Immerseel et al, 2002a). In feed, preparations of organic acids can reduce the chance of flock infection both from contaminated feed and environmental challenge (Humphrey and Lanning, 1988;de Olivera et al, 2000) but the efficiency of different products varies (Hume et al, 1993) and those containing the highest levels of free-formic acid in a liquid application appear to perform best.…”
Section: Feed and Water Treatmentsmentioning
confidence: 99%
“…in poultry are described but most require more large scale field evaluations (van Immerseel et al, 2002). In feed, preparations of organic acids can reduce the chance of flock infection both from contaminated feed and environmental challenge (Humphrey and Lanning, 1988;de Olivera et al, 2000) but the efficiency of different products varies (Hume et al, 1993) and those containing the highest levels of free-formic acid in a liquid application appear to perform best.…”
Section: Feed and Water Treatmentsmentioning
confidence: 99%